Deformation Monitoring and Stability Analysis of Shaft Lining in Weakly Cemented Stratum - Xianzhou Lyu; Weiming Wang (Advances in Civil Engineering)
Shaft linings in thick weakly cemented stratum have the disadvantages of large deformation and repeated damage after repair. Considering the typical geologic characteristics and the failure characteristics of shaft linings, we establish a multilayer automatic deformation monitoring system in this paper, and the monitoring system can realize the real-time, continuous, and long-term dynamic monitoring on shaft linings. Based on the concrete strength failure criterion under biaxial compression and the analytical solution for spatially axisymmetric problem of thick-wall cylinders, the damage limit of the shaft lining in Xieqiao coal mine is obtained. Then, we choose three sections as the test area according to the typical damage forms of shaft linings to carry out the monitoring scheme on the auxiliary shaft in Xieqiao coal mine. The monitoring results show that the extreme value of the shaft lining deformation is 2.369 mm. And the shaft lining located in the border between the floor aquifer and the bedrock generates the most severe deformation, which is about 89.4% of the deformation limit. The shaft lining deformation increment fluctuates in certain range, which belongs to elastic deformation. Finally, we inverse the stress state according to the deformation value of the shaft lining, and the obtained additional stress is found to be lower than the ultimate compressive strength. Long-term project practice confirms that the deformation monitoring results can reflect the real stress condition of the shaft lining and that the monitoring system can realize the real-time dynamic evaluation for the status of the shaft lining.